Defense Policy in the Link between National Policy and National Interest - Endro Tri Susdarwono; Aswhar Anis (Amal Insani Foundation, 2024)
There is a difference between making public policies related to defense and non-defense, the main consideration of making decisions in the field of defense is that in addition to the national interest, it must also be able to define threats that will be faced or potential to be faced. The approach in this study uses a descriptive approach, the approach is intended to describe or describe defense policies in the link between national policies and national interests, while the type of research is descriptive qualitative research. Defense Policy is one of the public policies, namely policies made by the government as a policy maker to achieve certain goals in society where in its preparation through various stages. Defense policy should always consider the national interest. The national interest has a close relationship with nationalism, aspects of the national interest include: humans who govern the nation and state democratically make decisions based on the best interests of the community or nation and state.